Unreported world ghost warriors - Kittel, Paul; Journeyman Pictures; Menton Oxford ([United Kingdom] : Menton Oxford, 2004)
This video discover the crisis in south Thailand. The Thai government blames Islamic separatists for rising tensions in the south. But police brutality is isolating the Muslim population
Title from title screen
Executive producer, Eamonn Matthews ; reporter, Sandra Jordar ; graphics, Roger Klumdy ; music, Jason Osborn
Keywords: Terrorism -- Thailand; Political violence